Prices in Robert Estienne’s booksellers’ catalogues (Paris 1541-1552): a statistical analysis - Goran Proot (JLIS.it, 2018)
This survey focuses on prices as they were advertised by the Paris printer and bookseller Robert Estienne in nine booksellers’ catalogues published between 1541 and 1552. 1,801 entries in total were entered onto a database; it has been possible to identify 77% of these from references to them in bibliographies, catalogues or other, mainly online, tools (in particular the Universal Short Title Catalogue, USTC). After exclusion of incomplete or doubtful data, 1,087 entries were selected for statistical analysis, in order to attempt to reveal overall trends as well as some of the main factors influencing prices of ‘first-hand’ (i.e., not second-hand), unbound books. These factors include the year of publication, the ‘age’ of editions, bibliographical format and use of any specific founts, such as Hebrew and Greek. Our analysis shows that prices of the majority of the editions mentioned more than once across different catalogues remained stable. In 13% of the cases for which enough data is present, prices varied. The results of this survey help us to understand something about the general price levels of books in Paris in this period, which in turn will help us develop a deeper understanding of the book trade on a wider scale in both time and space.